Handling tradeoffs between agile and usability methods - Butt, S.M. (Institute of Electrical and Electronics Engineers Inc., 2014)
In the past few years, many organizations have tried to improve their software development methodology. Different development approaches had been introduced but only a few are still functioning in the software industry. Agile software development is one approach, which is currently successful in software industry. For the development of interactive and usable software, this agile approach needs to integrate with usability approaches. But this integration is not clear as both agile and usability follows iterative approach of development while agile approach is more toward on writing code and development of a running system; whereas, usability focused on the user interface to make the software more usable and increase its usability by following UCD process. This paper provides an extensive related work on the integration of agile methods with usability that highlights critical issues in agile methods and shows the importance of usability in agile methods. In the end, the proposed model is discussed to handle tradeoff between usability and agile methods under one model. Â© 2014 IEEE.